2020
DOI: 10.1038/s41598-019-56877-y
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 controls Schwann cell self-organization through fibronectin fibrillogenesis

Abstract: The extracellular matrix is known to modulate cell adhesion and migration during tissue regeneration. However, the molecular mechanisms that fine-tune cells to extra-cellular matrix dynamics during regeneration of the peripheral nervous system remain poorly understood. Using the RSC96 Schwann cell line, we show that Sox2 directly controls fibronectin fibrillogenesis in Schwann cells in culture, to provide a highly oriented fibronectin matrix, which supports their organization and directional migration. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…However, the reduction in cell-cell adhesion was claimed to be partly due to the loss of E-cadherin expression and the enhanced expression of N-cadherins, which is not expressed in these cells, as reported by Smolyakov and colleagues [49], suggesting that other adhesion receptors may be implicated. Sox2 has also been shown to affect cell-ECM interactions in other systems, for example, cell adhesion-and ECM-related genes were found to be significantly up-regulated upon Sox2 overexpression in Schwann cells, and Sox2 was identified as a key regulator of ECM remodeling during Schwann cell clustering, directional migration, and axonal guidance in vitro [52].…”
Section: Discussionmentioning
confidence: 99%
“…However, the reduction in cell-cell adhesion was claimed to be partly due to the loss of E-cadherin expression and the enhanced expression of N-cadherins, which is not expressed in these cells, as reported by Smolyakov and colleagues [49], suggesting that other adhesion receptors may be implicated. Sox2 has also been shown to affect cell-ECM interactions in other systems, for example, cell adhesion-and ECM-related genes were found to be significantly up-regulated upon Sox2 overexpression in Schwann cells, and Sox2 was identified as a key regulator of ECM remodeling during Schwann cell clustering, directional migration, and axonal guidance in vitro [52].…”
Section: Discussionmentioning
confidence: 99%
“…They migrate and differentiate from neural crest cells and develop into precursor SCs that enter the SC 10 . Recent studies have reported an association between the up-regulation of transcription factor sox2 and the entry of neural crest precursor cells into the SC lineage [11][12][13] . In addition, transcription factor FoxD3 might be an important factor for the differentiation of neural crest cells into the SC lineage.…”
Section: Overview Of Schwann Cellsmentioning
confidence: 99%
“…In addition to proliferation and differentiation of neural crest cells into the SC lineage, sox10 also regulates the myelination of SCs 15 . These transcription factors might affect TN by regulating Schwann cell regeneration and myelin formation 12,16,17 . With extensive cell proliferation and differentiation, the SCs separate the axons into bundles, a process known as "radial sorting."…”
Section: Overview Of Schwann Cellsmentioning
confidence: 99%
See 2 more Smart Citations